2015
DOI: 10.1038/srep12449
|View full text |Cite
|
Sign up to set email alerts
|

Stomatal closure is induced by hydraulic signals and maintained by ABA in drought-stressed grapevine

Abstract: Water saving under drought stress is assured by stomatal closure driven by active (ABA-mediated) and/or passive (hydraulic-mediated) mechanisms. There is currently no comprehensive model nor any general consensus about the actual contribution and relative importance of each of the above factors in modulating stomatal closure in planta. In the present study, we assessed the contribution of passive (hydraulic) vs active (ABA mediated) mechanisms of stomatal closure in V. vinifera plants facing drought stress. Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
173
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(212 citation statements)
references
References 72 publications
13
173
0
6
Order By: Relevance
“…On the contrary, in AM+ plants upon both NS and WS conditions, and in control plants upon NS conditions, no significant differences in endogenous ABA levels were detected, a result supported by the absence of transcriptional changes in the selected genes of the ABA core signaling pathway. In woody plants, such as grapevine, it has been demonstrated that stomatal closure can be driven both by active (ABA-mediated) and/or passive (hydraulicsmediated) mechanisms (Tombesi et al, 2015). Our results, showing that ABA concentrations remain low in AM+ plants, raise the question of whether an involvement of hydraulics-mediated mechanisms in the regulation of stomatal closing under WS could be proposed for mycorrhizal tomato too.…”
Section: Aba Content and The Expression Of Aba-responsive Genesmentioning
confidence: 40%
“…On the contrary, in AM+ plants upon both NS and WS conditions, and in control plants upon NS conditions, no significant differences in endogenous ABA levels were detected, a result supported by the absence of transcriptional changes in the selected genes of the ABA core signaling pathway. In woody plants, such as grapevine, it has been demonstrated that stomatal closure can be driven both by active (ABA-mediated) and/or passive (hydraulicsmediated) mechanisms (Tombesi et al, 2015). Our results, showing that ABA concentrations remain low in AM+ plants, raise the question of whether an involvement of hydraulics-mediated mechanisms in the regulation of stomatal closing under WS could be proposed for mycorrhizal tomato too.…”
Section: Aba Content and The Expression Of Aba-responsive Genesmentioning
confidence: 40%
“…Hydraulic and biochemical signals are involved in stomatal control (Tardieu et al, 2010;Torres-Ruiz et al, 2015). Yet, the integrated understanding of stomatal control is still poor (Brodribb & McAdam, 2011), and therefore modelling approaches remain fragmental (Damour et al, 2010;Tombesi et al, 2015). The hydraulic theory states that under water deficit (decrease in soil water potential or increase in atmospheric demand) stomata close to prevent the formation of xylem embolisms (Damour et al, 2010).…”
Section: Stomatal Closurementioning
confidence: 99%
“…The hydraulic theory states that under water deficit (decrease in soil water potential or increase in atmospheric demand) stomata close to prevent the formation of xylem embolisms (Damour et al, 2010). Stomata can then be viewed as pressure regulators, buffering the drop of xylem water potential and the consequent risk of massive xylem embolism and catastrophic hydraulic failure (Tombesi et al, 2015). 4 sites in the Mediterranean region (e.g., Infante et al (1997) for Q. ilex near Seville, Spain).…”
Section: Stomatal Closurementioning
confidence: 99%
“…For example, drought treatment to roots causes leaf growth inhibition and stomatal behavior modification together with leaf cell-wall-hardening via osmotically generated hydraulic signals and ABA. 13,[23][24][25] Inhibition of leaf growth is often a primary plant response to moderate water stress. 23,26 However, since we found no developmental abnormality in shoots of OsERF71 overexpression rice plants, it is not persuasive.…”
Section: Molecular Mechanisms Of the Oserf71-mediated Drought Tolerancementioning
confidence: 99%